One-way fluid structure interaction analysis of a static savonius hydrokinetic turbine under different velocity and surface roughness with different blade materials - Mat Yazik M.H.; Zawawi M.H.; Ahmed A.N.; Sidek L.M.; Basri H.; Ismail F. (Elsevier Ltd, 2025)
Hydrokinetic turbines are prone to a harsh hydrodynamic environment with intricate vortical flows that elevate the probability of failure. The degradation of the blade surface caused by corrosion can impact the blade's hydrodynamic and the structural performance. This paper reports a one-way three-dimensional fluid-structure interaction simulation to analyse the performance of a static Savonius hydrokinetic turbine at varying rotor positions, with different surface roughness and water velocities, in terms of coefficients of static torque, static torque, stresses, and blade deformation. The simulations revealed that the optimum position for the highest coefficient of static torque was at 15 (Cst = 0.30) in reference to the water flow. Increasing the water velocity from 0.4 ms?1 to 0.84 ms?1 improved the turbine static torque due to an increase in the kinetic energy. However, the presence of surface roughness has deterioration effects on the static torque coefficient due to a delayed separation which causes a drag reduction. The simulation predicted no structural failure at 0.4 ms?1 and 0.84 ms?1, but varying materials exhibited varying maximum principal stress and deformation, highlighting the significance of the early development of materials selection process. The maximum von Mises stress and deformation was obtained when the turbine is resting at 45 for aluminium blade ( = 1.05 MPa, = 5.6e?4 mm). The results of this study indicate suitable materials from a hydrodynamic and material perspectives for the construction of the Savonius hydrokinetic turbine, which can be implemented in the design process to potentially save cost and minimize turbine downtime. ? 2023 Elsevier Ltd